The habit of art : best stories from the Indiana University fiction workshop - Ardizzone, Tony (Book collections on Project MUSE., 2005)
""The scientist has the habit of science; the artist, the habit of art.""--Flannery O'ConnorThis collection of stories contains some of the best new short fiction from America. The stories display a wide range of styles, settings, and themes. In addition to being among the country's most talented, prize-winning writers, the authors gathered in The Habit of Art also share a common bond as former members of the fiction workshop at Indiana University, which celebrates its first 25 years with the